A Modeling Approach that Integrates Individual Behavior, Social Networks, and Cross-Cultural Variation. Issue 10 (October 2019) - Smaldino, Paul E.
Abstract : How do psychological traits shape social networks? How does this relationship influence the spread of behavior? In a recent paper, Muthukrishna and Schaller ( Pers. Soc. Psychol. Rev., 2019) use a modeling approach to explore these questions. In doing so, they illustrate the value of using a multilevel approach to study human behavior.